Early childhood education and care (ECEC) during COVID‐19 boosts growth in language and executive function. Issue 4 (21st May 2021) - Davies, Catherine; Hendry, Alexandra; Gibson, Shannon P.; Gliga, Teodora; McGillion, Michelle; Gonzalez‐Gomez, Nayeli
Abstract: High‐quality, centre‐based education and care during the early years benefit cognitive development, especially in children from disadvantaged backgrounds. During the COVID‐19 pandemic and its associated lockdowns, access to early childhood education and care (ECEC) was disrupted. We investigate how this period affected the developmental advantages typically offered by ECEC. Using parent‐report data from 189 families living in the UK, we explore associations between time spent in ECEC by 8‐to‐36‐month‐olds, their socioeconomic background, and their growth in language and executive functions between Spring and Winter 2020. Receptive vocabulary growth was greater in children who continued to attend ECEC during the period, with a stronger positive effect for children from less advantaged backgrounds. The growth of cognitive executive functions (CEFs) was boosted by ECEC attendance during the period, regardless of socioeconomic background. Our findings highlight the importance of high‐quality ECEC for the development of key skills and for levelling socioeconomic inequalities.